Decreasing Door Danger Zones - Hal S. Knowles, III; Kathleen C. Ruppert; Karla A. Lenfesty; Barbara Haldeman (EDIS)
ABE-378, a 2-page fact sheet by Hal S. Knowles, III, Kathleen C. Ruppert, Karla A. Lenfesty, and Barbara Haldeman, is part 5 in the Education + Action = Wind Damage Mitigation series. It contains information on decreasing door danger zones. Published by the UF Department of Agricultural and Biological Engineering, November 2005.